Migração internacional: uma fuga da queda social? - Silva, Vini Rabassa da; Medeiros, Mara Rosange Acosta de; Ferreira, Simaia de Figueiredo (Emancipação, 2025)
Este artigo apresenta dados de uma pesquisa sobre Migrações Internacionais. Com o apoio da Cibercultura, o estudo realizado utilizou como ferramentas o Orkut e o MSN, que possibilitaram a aproximação com emigrantes residentes em diferentes países. Os resultados da pesquisa demonstram a existência de uma conexão das repercussões da globalização, particularmente no que tange ao desemprego estrutural e à perda do poder aquisitivo dos moradores da região sul do Estado do Rio Grande do Sul, com a decisão de emigrar. Palavras-chave: Migrações internacionais. Globalização. <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">Desemprego. <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US"> <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">Abstract: This article presents data of a study about International Migrations. With the support of the cybernetic culture, the accomplished study used as tools the Orkut and the MSN sites, which allowed the approximation of resident emigrants in different countries. The results of the study show a connection in the repercussions of the globalization, particularly in relation to the structural unemployment and the loss of the purchasing power of the residents of the southern region of Rio Grande do Sul State, with the decision to emigrate. <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">Keywords: International migration. Globalization. Unemployment.